Young Children From Three Diverse Cultures Spontaneously and Consistently Prepare for Alternative Future Possibilities. Issue 1 (8th May 2018) - Redshaw, Jonathan; Suddendorf, Thomas; Neldner, Karri; Wilks, Matti; Tomaselli, Keyan; Mushin, Ilana; Nielsen, Mark
Abstract : This study examined future‐oriented behavior in children (3–6 years; N = 193) from three diverse societies—one industrialized Western city and two small, geographically isolated communities. Children had the opportunity to prepare for two alternative versions of an immediate future event over six trials. Some 3‐year‐olds from all cultures demonstrated competence, and a majority of the oldest children from each culture prepared for both future possibilities on every trial. Although there were some cultural differences in the youngest age groups that approached ceiling performance, the overall results indicate that children across these communities become able to prepare for alternative futures during early childhood. This acquisition period is therefore not contingent on Western upbringing, and may instead indicate normal cognitive maturation.